PLCε1 suppresses tumor growth by regulating murine T cell mobilization. (9th January 2020) - Strazza, M.; Adam, K.; Smrcka, A. V.; Lerrer, S.; Mor, A.
Summary: Phospholipase C epsilon 1 (PLCε1) is a unique member of the phospholipase family, in that it also functions as a guanine nucleotide exchange factor (GEF) for the small GTPase Rap1. It is this function as a Rap1 GEF that gives PLCε1 an essential role in chemokine‐mediated T cell adhesion. We have utilized a syngeneic tumor model, MC38 cells in C57BL/6 mice, and observed that tumors grow larger and more quickly in the absence of PLCε1. Single‐cell analysis revealed an increased CD4 + /CD8 + ratio in the spleens, lymph nodes and tumors of PLCε1 knock‐out tumor‐bearing mice. T cells isolated from PLCε1 knock‐out mice were less activated by multiple phenotypical parameters than those from wild‐type mice. We additionally noted a decrease in expression of the chemokine receptors C‐X‐C chemokine receptor type 4 (CXCR4) and C‐C motif chemokine receptor 4 (CCR4) on CD4 + T cells from the spleens, lymph nodes and tumors of PLCε1 knock‐out mice compared to wild‐type mice, and diminished migration of PLCε1‐depleted CD3 + T cells towards stromal cell‐derived factor (SDF)‐1α. Based on these results, we conclude that PLCε1 is a potential regulator of tumor‐infiltrating lymphocytes, functioning, at least in part, at the level of T cell trafficking and recruitment. Abstract : We discovered that tumors grow larger in the absence of the enzyme PLCε1. Importantly, and despite the fact that PLCe1 deficient T cells are intrinsically cytotoxic, they cannot migrate toward the inflammatory tumor environment, a finding that is also supported by abnormal expression of several chemokine receptors. Thus, PLCε1 is a potential regulator of tumor infiltrating lymphocytes, functioning at the level of T cell trafficking and recruitment.